2021
DOI: 10.1007/s10488-021-01171-1
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Exploration of the Views of Policymakers and Policy Advisors on the Impact of Mental Health Stigma on the Development and Implementation of Mental Health Policy in Singapore

Abstract: Few studies have examined the views of policy makers regarding the impact of mental health stigma on the development and implementation of mental health policies. This study aimed to address this knowledge gap by exploring policymakers’ and policy advisors’ perspectives regarding the impact of mental health stigma on the development and implementation of mental health programmes, strategies, and services in Singapore. In all 13 participants were recruited for the study comprising practicing policymakers, senio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…All included studies were published between 2018 and 2022, and all but three used qualitative research methodology. One study used a phenomenological approach (Tristiana et al, 2018) and eight studies used semi‐structured interviews (Gunasekaran et al, 2022; Hall et al, 2019; Nguyen et al, 2019; Parry et al, 2020; Putri et al, 2021; Subramaniam et al, 2021; Trang et al, 2021; Zay Hta et al, 2021). Of the remaining three studies, two were cross‐sectional studies (Charlson et al, 2019; Van et al, 2021) and one was a prospective cohort study (Trang et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All included studies were published between 2018 and 2022, and all but three used qualitative research methodology. One study used a phenomenological approach (Tristiana et al, 2018) and eight studies used semi‐structured interviews (Gunasekaran et al, 2022; Hall et al, 2019; Nguyen et al, 2019; Parry et al, 2020; Putri et al, 2021; Subramaniam et al, 2021; Trang et al, 2021; Zay Hta et al, 2021). Of the remaining three studies, two were cross‐sectional studies (Charlson et al, 2019; Van et al, 2021) and one was a prospective cohort study (Trang et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Poor health literacy, especially a lack of understanding about mental health, was reported in six studies (Hall et al, 2019;Nguyen et al, 2019;Parry et al, 2020;Putri et al, 2021;Subramaniam et al, 2021;Trang et al, 2021;Zay Hta et al, 2021). Hall et al (2019) and Zay Hta et al ( 2021) reported that the lack of available information contributed to the poor knowledge held by the SEA population, while Subramaniam et al (2021) identified that mental health education was a low priority in schools and workplaces. Three studies (Gunasekaran et al, 2022;Putri et al, 2021;Subramaniam et al, 2021) identified poor health literacy likely leading to further stigma, resulting in ongoing barriers to accessing mental health care.…”
Section: Poor Health Literacymentioning
confidence: 99%
See 3 more Smart Citations